(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
To address the limitations of the traditional idealized loop model, this study conducted experimental analysis and mathematical model for the morphological structure of the weft-knitted loop, and research on the method for describing the weft loop's structure and parameters. Because the features of the loop's structure is consistent with the Non-uniform Rational Basis Spline (NURBS), three degree NURBS curve was used to establish the model of the weft loop, and the corresponding value points' coordinate can be obtained by the experimental analysis of the effect of the fabric structure from the structure parameters. In addition, based on the features of the different weft-knitted structure, the models of plain and pattern stitch have been established. Research shows NURBS curve modeling can be applied to a more complex weft tissue as well as the basic and variation tissue.